The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1371/journal.pone.0239783
|View full text |Cite
|
Sign up to set email alerts
|

Tumor budding score predicts lymph node status in oral tongue squamous cell carcinoma and should be included in the pathology report

Abstract: Background The majority of oral cavity cancers arise in the oral tongue. The aim of this study was to evaluate the prognostic value of tumor budding in oral tongue squamous cell carcinoma, both as a separate variable and in combination with depth of invasion. We also assessed the prognostic impact of the 8th edition of the American Joint Committee on Cancer's TNM classification (TNM8), where depth of invasion (DOI) supplements diameter in the tumor size (T) categorization. Methods Patients diagnosed with prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 30 publications
1
28
0
5
Order By: Relevance
“…Regarding the emerging prognostic markers that are not included in the pathology report, the published studies revealed a promising prognostic value for cancer‐related histopathologic markers including cell‐in‐cell structures (one study), 19 tumor budding (seven studies), 13,15,25–29 and pattern of invasion (15 studies) which were evaluated either as mode of invasion, 22,30 pattern of invasion, 31–34 invasive pattern, 28 or WPOI 13,16,25,35–39 . At the same time, some of the relevant studies analyzed stromal‐related histopathologic markers including stromal infiltrating lymphocytes (one study) 18 and tumor–stroma ratio (TSR; three studies) 17,40,41 which were significantly associated with prognosis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the emerging prognostic markers that are not included in the pathology report, the published studies revealed a promising prognostic value for cancer‐related histopathologic markers including cell‐in‐cell structures (one study), 19 tumor budding (seven studies), 13,15,25–29 and pattern of invasion (15 studies) which were evaluated either as mode of invasion, 22,30 pattern of invasion, 31–34 invasive pattern, 28 or WPOI 13,16,25,35–39 . At the same time, some of the relevant studies analyzed stromal‐related histopathologic markers including stromal infiltrating lymphocytes (one study) 18 and tumor–stroma ratio (TSR; three studies) 17,40,41 which were significantly associated with prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…The meta‐analysis of OS revealed some heterogeneity ( I 2 = 44%). For DSS, two studies 15,25 were included in the meta‐analysis and are visualized using a forest plot (Figure 2B). Again, tumor budding was indicated to be a predictor of DSS (HR 1.89, 95% CI 1.13–3.15; p = 0.02).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The major pitfalls of our study are its retrospective nature, lack of centralized pathology revision, and the lack of a pathological nodal staging for half of the patients. Moreover, other prognosticators such as the pattern of invasion, PNI density foci, and tumor budding, which were recently demonstrated to be expression of tumor biological behavior, were not available [ 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Piazza et al (2019) and Bjerkli et al (2020) suggested that the 8th edition of the AJCC staging system improved the prognostic value of the T category than the previous one in early-stage oral tongue SCC [ 19 , 20 ]. Contrary to Piazza et al (2019) and Bjerkli et al (2020), our results are more relevant to Kano et al (2018) As this study included a relatively small number of patients and all oral cavity subsites, additional studies using a larger patient population are needed.…”
Section: Discussionmentioning
confidence: 99%